2014
DOI: 10.1111/joor.12192
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis of the Oral Health Impact Profile

Abstract: Although oral health-related quality of life (OHRQoL) as measured by the Oral Health Impact Profile (OHIP) is thought to be multidimensional, the nature of these dimensions is not known. The aim of this report was to explore the dimensionality of the OHIP using the Dimensions of OHRQoL (DOQ) Project, an international study of general population subjects and prosthodontics patients. Using the project's Learning Sample (N=5,173), we conducted an exploratory factor analysis on the 46 OHIP items not specifically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 28 publications
4
152
2
3
Order By: Relevance
“…They form a ''dimension'' ('Orofacial pain' dimension 25,33 ) of the OHRQoL, i.e., an important and distinct area within the umbrella construct OHRQoL. These quantitative findings 25,33 ) are also borne out by more qualitative findings 4,12,34 that suggest a dimension for pain in the stomatoganthic system as opposed to the current, more generic, ''Physical pain'' domain in the OHIP-49 is required. This would explain why several pains correlate and cluster together in terms of impact on the OHRQoL.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…They form a ''dimension'' ('Orofacial pain' dimension 25,33 ) of the OHRQoL, i.e., an important and distinct area within the umbrella construct OHRQoL. These quantitative findings 25,33 ) are also borne out by more qualitative findings 4,12,34 that suggest a dimension for pain in the stomatoganthic system as opposed to the current, more generic, ''Physical pain'' domain in the OHIP-49 is required. This would explain why several pains correlate and cluster together in terms of impact on the OHRQoL.…”
Section: Discussionmentioning
confidence: 87%
“…We elected not to examine the seven domains of the OHIP-49 and just use the simple summary score as recommended by the Dimensions of OHRQoL (DOQ) project because of methodological weaknesses in the domain scores 25 . In the present study, we therefore use the simple sum of the 49 item's response codes as our OHRQoL measure.…”
Section: Assessment Of Ohrqolmentioning
confidence: 99%
“…The Dimensions of OHRQoL Project [7] suggested, based on exploratory factor analytic results from 5,173 international participants and confirmatory factor analytic results from 5,022 participants, that Oral Function , Orofacial Pain , Orofacial Appearance , and Psychosocial Impact are the four major aspects of patient’s self-perceived OHRQoL [16, 17] that are measured by the OHIP. However, the findings of the DOQ Project caution against the use of four dimension-scores due to the presence of a large general factor that accounts for the lion’s share of reported symptom/problem comorbidity.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to clinical parameters of oral health, such as caries prevalence or degree of malocclusion, these measures offer a complementary view of how patients perceive their oral health status. A recent study found four factors of OHRQoL: oral function, oro-facial pain, oro-facial appearance, and psychosocial impact [2,3]. These factors or dimensions represent the more detailed aspects regarding patients' perceived oral health.…”
Section: Introductionmentioning
confidence: 99%